Test and Verification of AES Used for Image Encryption - Zhang, Yong (3D research, 2018)
In this paper, an image encryption program based on AES in cipher block chaining mode was designed with C language. The encryption/decryption speed and security performance of AES based image cryptosystem were tested and used to compare the proposed cryptosystem with some existing image cryptosystems based on chaos. Simulation results show that AES can apply to image encryption, which refutes the widely accepted point of view that AES is not suitable for image encryption. This paper also suggests taking the speed of AES based image encryption as the speed benchmark of image encryption algorithms. And those image encryption algorithms whose speeds are lower than the benchmark should be discarded in practical communications. Graphical Abstract Image cryptosystem based on AES in CBC mode